Investigation of mental health of amateur and professional football players in the COVID-19 pandemic period - Akgün, H.; Biçer, M.; Vural, M. (European Journal of Physical Education and Sport Science, 2021)
The aim of this study is to investigate the mental health of amateur and professional football players during the Covid-19 pandemic period. For this purpose, 49 amateur female, 68 amateur male and 34 professional male football players participated in the study. The Pittsburgh Sleep Quality Index consisting of 24 questions and the Beck Depression Scale consisting of 21 questions were applied to measure the sleep quality and depression symptoms of the participants. The obtained data were analyzed with the SPSS 22.0 program. Values were presented as minimum, maximum, mean, standard deviation, and standard error. Significance level was accepted as p<0.05. The Kolmogorov-Smirnov test was used to test for normality. One Way Anova and LSD tests were performed to analyze the differences between groups. There were significant differences in BDI total score, subjective sleep quality and sleep disorder parameters when grouped by age. (p<0.05) Significant differences were found in BDI total score, subjective sleep quality, sleep latency, sleep disturbance, and total PUKI score parameters when grouped by sport categories. (p<0.05) No significant difference was found in any parameter in grouping the participants according to sports age. (p>0.05) As a result, it can be said that the sleep quality of amateur women and amateur men is bad, and the sleep quality of professional men is good during the Covid-19 pandemic period. It can be said that the depression symptoms of amateur women are bad, the amateur men's group is moderate, and the depression symptoms of professional men are good.